Association of α 1 Antitrypsin Phenotype and Development of Advanced Liver Disease and Pulmonary Complications Before and After Liver Transplantation. Issue 7 (July 2021) - Abu Rmilah, Anan; Fencl, Robert; Watt, Kymberly; Krowka, Michael; Wiesner, Russell; Murray, David; Nyberg, Scott; Leise, Michael
Abstract : Background: The role of MZ phenotype of α 1 antitrypsin (α1AT) deficiency as a potential cofactor in advanced liver disease arising from other primary causes is not widely understood. In the general population, MZ phenotype accounts for 2%–4% in Europe and 2%–7.1% in North America. The aim of this study was to determine the prevalence of the MZ phenotype among various causes of cirrhosis in the United States in the modern era and its impact on pulmonary function before and after liver transplantation. Methods: This retrospective study included adult patients with cirrhosis who underwent liver transplantation at Mayo Clinic. Participants' data including pathogenesis of cirrhosis, model for end-stage liver disease-Na score, α1AT phenotype, liver decompensation events, and pulmonary outcomes was determined by retrospective review of the liver transplantation database. Results: One hundred thirty of 1341 adult patients with cirrhosis (9.7%) were α1AT MZ carriers. When comparing the distribution of protease inhibitor (PI) MZ among different pathogenesis, the prevalence of MZ was significantly increased in nonalcoholic steatohepatitis (NASH), alcoholic liver disease (ALD), and cryptogenic cirrhosis compared with other causes. Thirty-seven of 171 with NASH (22%), 37 of 187 with ALD (20%), and 9 of 39 with cryptogenic cirrhosis (23.1%) were identified as PI MZ, while in other subgroups; we detected 18 of 320 with viral hepatitis, and 11 of 339 with primary biliary cholangitis/primary sclerosing cholangitis. Also, MZ patients were more likely to develop preoperative chronic obstructive lung disease, and postoperative pulmonary hypertension and pulmonary embolism than MM patients. Conclusions: The rates of preoperative and postoperative pulmonary complications were found to be higher in PI MZ patients than in PI MM patients. The MZ phenotype was significantly enriched in NASH, ALD, and cryptogenic cirrhosis.